A efetivação do Direito ao Desenvolvimento como Direito Humano: uma análise dos programas incentivadores do desenvolvimento na Universidade Federal de Uberlândia e seu alinhamento junto aos Objetivos de Desenvolvimento Sustentável - Strack, Amanda Filsner Dias (2023)
This dissertation focuses on the analysis of student assistance programs at University of Uberlândia (UFU). The general objective is to answer the question if through these programs, the University promotes the Human Right to Development and how these programs align with the United Nations Sustainable Development Goals (SDGs). This case study explores the legislation that treats the subject, as well as the assistance programs that exist inside the Pro-Rectory of Student Assistance of the institution. A report on the History of Human Rights is presented, in addition to the conceptualization and construction of the terms sustainability and sustainable development. It presents a discussion on the concept of development from its inception to the idealization of the SDGs, and examines the assistance programs that help students to remain in a university, besides those that benefit the external community, linking them to the goals of the SDGs. The work tries to demonstrate the importance of the institution in promoting Human Development, through the pillars that measure the index of this development, such as income, education and health. The work method is deductive, because through a detailed analysis of the programs currently implemented at the Federal University of Uberlândia, it is possible to conclude that the institution seeks to implement the right to community development. The methods of procedure are the functionalist, which explains why student assistance programs are fundamental in structuring the development of the community and the statistical, because through oficial data, the objective is to verify the promotion of the Right to Development by the University. After analyzing the legislation and programs, the research concluded that UFU promotes the Human Right to Development, enabling income, health and education, besides proving that such programs are aligned with the UN SDGs.